The Effect of Financial Rewards, Religiosity, and Job Market Considerations on Student Interest in a Career in Islamic Financial Institutions - Regita Putri , Devara; Sam’ani, Sam’ani; Arumsari , Vita (Tazkia Islamic University College, 2023)
This study aims to analyze the significance of the influence of financial rewards, religiosity, and job market considerations on the interest of students of the Sharia Banking Study Program, Department of Accounting, Semarang State Polytechnic, to have a career in Islamic Financial Institutions both simultaneously and partially. The population in this study were students of the Sharia Banking Study Program, Department of Accounting, Semarang State Polytechnic. Using sampling techniques, namely purposive sampling and accidental sampling, there were 75 respondents who met the criteria. The data used in this study are primary data obtained through the dissemination of questionnaires. The analysis model used in this study is a multiple linear regression analysis model, while the analysis technique uses a statistical test F, a coefficient of determination test (R2), and a statistical test t that is processed using the SPSS 26.00 program. The results of proving hypotheses and discussions show that (1) Financial rewards, religiosity, and job market considerations simultaneously have a significant effect on students' interest in a career in Islamic Financial Institutions. (2) Financial rewards do not partially have a significant effect on the interest of students in a career in Islamic Financial Institutions. (3) Religiosity partially effects the interest of students in a career in Islamic Financial Institutions. (4) Consideration of the Job Market partially has a significant effect on the interest of students in a career in Islamic Financial Institutions.